FORMULAIC LANGUAGE OF TOURISM IN ENGLISH FOR ACADEMIC PURPOSE (EAP) COURSE BOOK: A CORPUS-DRIVEN APPROACH - Ehsan Namaziandost; Meisam Ziafar; Dwiniasih Dwiniasih (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2020)
One approach to taking advantage of corpora in language teaching would be adding to a textbook through enriching it through employing corpus-based research. When it comes to using English for Academic Purposes (EAP) materials, the inclusion of corpora in teaching language becomes even more urgent. In the current study, the authors did their best to investigate and describe the presence of formulaic language in an EAP textbooks titled: English for international tourism: Pre-intermediate students’ book written by Dubicka and O’keeffe (2003) through a case study, and corpus-driven method as a research methodology. Therefore, this study aims to investigate to what extent the EAP course book designed for tourism titled English for international tourism (EIT) is compatible with a corpus-driven formulaic approach. Findings show that this EAP textbook falls fairly short of presenting the necessary formulas as frequently employed in tourism English. Supplementing such materials with corpora and the formulaic they provide may boost the quality of EAP education and practice.